PELAYANAN SANTUNAN KECELAKAAN LALU LINTAS PADA PT. JASA RAHARJA(PERSERO) CABANG RIAU - Sinta Aulia; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The number of public transportation in society environment is increasing day by day. It can be seen from the increasing of the number of vehicle’s on the street as one of transportation means for human to go somewhere to fulfill their needs. This can give effects to the traffic safety, especially in traffic accidence. In order to follow up the victims of accident, government has made an insurance institution that has the program of giving sympathetic care services. The name of this institution is PT. Jasa Raharja (Persero) that also exists in Riau..The theory that is used in this service is told by Agus Dwiyanto that has seen services as 5 categories, they are: official behavior, procedure, time, facility, and the implementation of the services. The aim of this research is to know how the implementation of care services of traffic accident in PT. Jasa Raharja (Persero) Branch Riau and the factors that affect it. The method of this research is qualitative method by descriptive investigation. The data collection technique is interviewing, observation and documentation by using purposive sampling method as a source of information and the data analysis techniqueis triangular technique.The result of this research shows that the implementation of care services of traffic accident in PT. Jasa Raharja (Persero) Branch Riau has been well done as what has been expected. However, the facility is unequal to the expectation. Moreover, the implementation of the care service is affect by the shortage of identity data of society in reporting the claims. In order to make the implementation of care services can be maximal and comprehensive, PT Jasa Raharja (persero) is expected to improve the services and give the transparency to the victims of accident to report the problem to PT. Jasa Raharja.Key Words: Services, Sympathetic Care, Traffic Accident